2005
DOI: 10.1007/s10725-005-3380-6
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Plants of Creeping Bent Grass Harboring the Stress Inducible Gene, 9-cis-epoxycarotenoid dioxygenase, are Highly Tolerant to Drought and NaCl Stress

Abstract: Transgenic lines of creeping bent grass were generated by Agrobacterium-mediated transformation with the VuNCED1 which was cloned from cow pea has a homology to 9-cis-epoxycarotenoid dioxygenase, which is supposed to be involved in abscisic acid (ABA) biosynthesis. ABA, a cleavage product of carotenoids, is involved in stress responses in plants. The limiting step of ABA biosynthesis in plants is presumably the cleavage of 9-cis-epoxycarotenoids, the first committed step of ABA biosynthesis. Molecular analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 33 publications
(41 reference statements)
2
37
0
2
Order By: Relevance
“…There have been several studies on altering ABA levels by overexpression of ABA biosynthesis or catabolism genes using constitutive promoters. For example, transgenic overexpression of 9-cis-epoxycarotenoid dioxygenase (NCED) genes in tomato (Solanum lycopersicum), Arabidopsis, bean (Phaseolus vulgaris), and cowpea (Vigna unguiculata) enhances ABA content in leaves or whole plants and reduces transpiration (Thompson et al, 2000;Iuchi et al, 2001;Qin and Zeevaart, 2002;Aswath et al, 2005). However, ubiquitous expression causes growth retardation.…”
mentioning
confidence: 99%
“…There have been several studies on altering ABA levels by overexpression of ABA biosynthesis or catabolism genes using constitutive promoters. For example, transgenic overexpression of 9-cis-epoxycarotenoid dioxygenase (NCED) genes in tomato (Solanum lycopersicum), Arabidopsis, bean (Phaseolus vulgaris), and cowpea (Vigna unguiculata) enhances ABA content in leaves or whole plants and reduces transpiration (Thompson et al, 2000;Iuchi et al, 2001;Qin and Zeevaart, 2002;Aswath et al, 2005). However, ubiquitous expression causes growth retardation.…”
mentioning
confidence: 99%
“…The first dedicated step in ABA biosynthesis in plants is the oxidative cleavage of 9-cis-epoxycarotenoids, as catalyzed by 9-cis-epoxycarotenoid dioxygenase (NCED; Schwartz et al, 2003;Taylor et al, 2005). The maize gene VP14 was the first NCED gene to be cloned Tan et al, 1997), and when the orthologous genes from tomato (Solanum lycopersicum), Arabidopsis (Arabidopsis thaliana), bean (Phaseolus vulgaris), and cowpea (Vigna unguiculata) were overexpressed in plants, the ABA content of leaves or whole plants was enhanced (Thompson et al, 2000;Iuchi et al, 2001;Qin and Zeevaart, 2002;Aswath et al, 2005) and transpiration was reduced (Thompson et al, 2000;Iuchi et al, 2001;Qin and Zeevaart, 2002). ABA was also increased in seeds (Thompson et al, 2000) and germination was delayed (Thompson et al, 2000;Qin and Zeevaart, 2002).…”
mentioning
confidence: 99%
“…ABA was also increased in seeds (Thompson et al, 2000) and germination was delayed (Thompson et al, 2000;Qin and Zeevaart, 2002). Drought tolerance was noted, based on visual observation of transgenic tobacco and Arabidopsis plants when water was withheld (Iuchi et al, 2001;Qin and Zeevaart, 2002), while dry weight accumulation in creeping bent grass (Agrostis palustris) grown under drought or high salinity experiments was enhanced by overexpression of a cowpea NCED (Aswath et al, 2005). These studies all used constitutive promoters to drive expression of NCED genes.…”
mentioning
confidence: 99%
“…Several researches indicated that over-expression of NCED gene in transgenic plants enhance ABA accumulation and increases the tolerance to drought (Iuchi et al, 2001;Qin and Zeevaart, 2002;Aswath et al, 2005;Wan and Li, 2006;Zhang et al, 2008), and salt stress (Aswath et al, 2005;Zhang et al, 2008). CkNCED1 expression and ABA accumulation were maintained at a high level for a longer period under a variety of abiotic stresses, which indicates that C. korshinskii likely possesses strong stress tolerance.…”
Section: Discussionmentioning
confidence: 99%